2019
DOI: 10.4102/aej.v7i1.371
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of transport subsidisation: Comparing findings from a customer perception survey and Most Significant Change Technique interviews

Abstract: BackgroundPre-1994 spatial development policies that separated racial groups into geographically segregated neighbourhoods left South Africa with sprawling cities that increase the cost of public service delivery. Low-density areas in cities make transport networks extremely inefficient, resulting in high transport costs and long commuting hours, according to the Government Technical Advisory Centre (Republic of South Africa 2013:1), which has determined that '[t]he higher costs, combined with affordability co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…First, we found that the technique was suitable once adjusted to meet the time-sensitive evaluation needs of the small-scale [program]. Some evaluators suggest that the technique is not appropriate for time-sensitive evaluations ( Serrat, 2010 , Rabie and Burger, 2019 ), as time is essential to have discussions with multiple groups of program stakeholders and to repeat the process as required. In our case, one round of significant change data was sufficient to investigate potential outcomes of the newly remote program.…”
Section: Phase 3: Outcome Evaluationmentioning
confidence: 99%
“…First, we found that the technique was suitable once adjusted to meet the time-sensitive evaluation needs of the small-scale [program]. Some evaluators suggest that the technique is not appropriate for time-sensitive evaluations ( Serrat, 2010 , Rabie and Burger, 2019 ), as time is essential to have discussions with multiple groups of program stakeholders and to repeat the process as required. In our case, one round of significant change data was sufficient to investigate potential outcomes of the newly remote program.…”
Section: Phase 3: Outcome Evaluationmentioning
confidence: 99%
“…Fundamentally a narrative method, MSC garners rich qualitative data and is more complex than it seems ( Willetts & Crawford, 2007 ). While sometimes used as a sole evaluation tool (see, for example, Aisiri et al, 2020 ), triangulation with quantitative methods is strongly recommended ( Davies & Dart, 2005 ; Ho et al, 2015 ; Rabie & Burger, 2019 ).…”
Section: The Most Significant Change Techniquementioning
confidence: 99%
“…Even so, MSC has been widely applied to evaluation projects within Australia and internationally; however, the majority are described in grey literature, which can be difficult to access ( Tonkin et al, 2021 ; Willetts & Crawford, 2007 ). Some examples appearing in academic publications include a professional development initiative for Australian teachers ( Heck & Sweeney, 2013 ); customer perceptions of a transport subsidisation programme in South Africa ( Rabie & Burger, 2019 ); and water and sanitation projects in Laos ( Willetts & Crawford, 2007 ).…”
Section: The Most Significant Change Techniquementioning
confidence: 99%
“…Given the profusion of sites and organizations involved in the project, an adapted version of the most significant change participatory interview method was used to capture the perceptions of the individuals and organizations involved. This method involves the collection of stories from those involved in the fieldwork (Davies & Dart, 2005) and has been used as a monitoring and evaluation tool to facilitate inclusive project reflection, learning and adaptation in diverse disciplines, including conservation (Wilder & Walpole, 2008), development (Kraft & Prytherch, 2016) and government policy delivery (Rabie & Burger, 2019).…”
Section: Introductionmentioning
confidence: 99%